2018
DOI: 10.1093/annonc/mdy009
|View full text |Cite
|
Sign up to set email alerts
|

Unique genetic profiles from cerebrospinal fluid cell-free DNA in leptomeningeal metastases of EGFR-mutant non-small-cell lung cancer: a new medium of liquid biopsy

Abstract: CSF cfDNA could reveal the unique genetic profiles of LM and should be considered as the most representative liquid biopsy medium for LM in EGFR-mutant NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
277
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(293 citation statements)
references
References 19 publications
15
277
1
Order By: Relevance
“…In the present study, consistent with previously reported findings, our results also reveal that MPE supernatant is a superior sample to MPE cell pellet, based on both mutation detection rate and median maxAF value. Moreover, our findings are also in agreement with a recent report of the superiority of cell‐free DNA derived from CSF, compared to its corresponding cell pellet . It has been reported that the fraction of tumor‐derived DNA is significantly higher in the supernatant than its corresponding cell pellet in CSF .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, consistent with previously reported findings, our results also reveal that MPE supernatant is a superior sample to MPE cell pellet, based on both mutation detection rate and median maxAF value. Moreover, our findings are also in agreement with a recent report of the superiority of cell‐free DNA derived from CSF, compared to its corresponding cell pellet . It has been reported that the fraction of tumor‐derived DNA is significantly higher in the supernatant than its corresponding cell pellet in CSF .…”
Section: Discussionsupporting
confidence: 93%
“…NGS libraries were prepared according to a previous publication . A minimum of 50 ng of DNA was required for NGS library construction.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of EGFR ‐driven genes, the results from brain lesion tissues were consistent with those from CSF, as supported by Li et al . The detection of EGFR mutations in CSF might also reveal uncommon EGFR mutations that could be targeted with specific treatments .…”
Section: Discussionsupporting
confidence: 72%
“…Variant gene mutations of tumor cells often lead to different proliferation activities, and the location of the resulting metastasis may also differ . Recently, studies indicated that CSF was more representative of the EGFR mutation status in brain metastasis than peripheral blood and could better guide medical treatments . Nevertheless, that previous study did not evaluate the genetic characteristics of lung cancer with brain metastasis in cotesting of lung tumor tissue, brain metastases, peripheral blood, and CSF.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the invasiveness and difficulty of obtaining BM samples, the molecular mechanisms and evolution of BMs have not been extensively studied in lung cancer. 11 However, additional studies including larger patient cohorts need to be performed. 11 However, additional studies including larger patient cohorts need to be performed.…”
Section: Introductionmentioning
confidence: 99%